2019
DOI: 10.1002/ijc.32027
|View full text |Cite
|
Sign up to set email alerts
|

Laminin γ2‐enriched extracellular vesicles of oral squamous cell carcinoma cells enhance in vitro lymphangiogenesis via integrin α3‐dependent uptake by lymphatic endothelial cells

Abstract: Oral squamous cell carcinoma (OSCC) LN1‐1 cells previously showed greater capacities for lymphangiogenesis and lymph node metastasis compared to their parental OEC‐M1 cells, in addition to an ability to enhance the migration and tube formation of lymphatic endothelial cells (LECs). Purified by a series of differential centrifugations and characterized using electron microscopy, dynamic light scattering and western blot, LN1‐1 cell‐derived extracellular vesicles (LN1‐1 EVs) were shown to promote LEC migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Laminin-332 in cancer cells has been shown to promote cell growth, invasion and metastasis [55]. In accord with this, Wang et al (2019) [44] found that Laminin-332 proteins (laminin α3, β3 and γ2) were upregulated in LN1-1 cell line EVs versus the levels found in the EV of the OEC-M1 cell line, from which LN1-1 cells were derived (>1.5 fold) and the number of laminin γ2-positive gold particles per EV was greater in LN1-1 EVs than in OEC-M1 EVs (p < 0.01) [44]. Comparing 10 healthy controls and 20 OSCC, ELISA detected a significantly higher level of plasma EV-borne laminin-332 in lymph node positive OSCC patients than in lymph node negative OSCC patients, which were both higher than healthy controls (p < 0.01).…”
Section: Differential Expression Of Oscc-derived Ev Surface and Cargomentioning
confidence: 90%
See 2 more Smart Citations
“…Laminin-332 in cancer cells has been shown to promote cell growth, invasion and metastasis [55]. In accord with this, Wang et al (2019) [44] found that Laminin-332 proteins (laminin α3, β3 and γ2) were upregulated in LN1-1 cell line EVs versus the levels found in the EV of the OEC-M1 cell line, from which LN1-1 cells were derived (>1.5 fold) and the number of laminin γ2-positive gold particles per EV was greater in LN1-1 EVs than in OEC-M1 EVs (p < 0.01) [44]. Comparing 10 healthy controls and 20 OSCC, ELISA detected a significantly higher level of plasma EV-borne laminin-332 in lymph node positive OSCC patients than in lymph node negative OSCC patients, which were both higher than healthy controls (p < 0.01).…”
Section: Differential Expression Of Oscc-derived Ev Surface and Cargomentioning
confidence: 90%
“…Comparing 10 healthy controls and 20 OSCC, ELISA detected a significantly higher level of plasma EV-borne laminin-332 in lymph node positive OSCC patients than in lymph node negative OSCC patients, which were both higher than healthy controls (p < 0.01). The protein load ex vivo fluorescent signals from the cervical lymph nodes of mice orthotopically implanted with PKH-26-labeled laminin γ2-deficient EVs (from LN1-1 LAMC2-knockdown cells) demonstrated a significant decrease in uptake relative to the corresponding controls (p < 0.01), suggesting a reduced ability to drain into lymph nodes in comparison with the control EVs [44].…”
Section: Differential Expression Of Oscc-derived Ev Surface and Cargomentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the level of PD-L1 carried by plasma exosomes instead of soluble PD-L1 level was correlated with disease severity, the UICC stage and the lymph node status [64]. Moreover, Wang et al have identified a higher expression of laminin-332 in plasma exosomes from OSCC patients with lymph node metastasis [65]. Li et al found that serum exosomal miR-21 level was closely associated with HIF-1a/HIF-2a expression, T stage, and lymph node metastasis [20].…”
Section: Circulating Exosomes In Osccmentioning
confidence: 96%
“…In Kozaki and colleagues' study, they found that the increase of HSP90-rich exosomes is positively correlated to the increased invasive capacity of OSCC; moreover the knockdown of HSP90α and HSP90β decreased the metastatic capacity and survivability of OSCC cells (Ono et al 2018). Observing that OSCC LN1-1 cells were more aggressive in lymphatic node metastasis than OEC-M1 cells, Wang et al used stable isotope amino acid labeling to reveal that higher laminin-332 protein levels in tumor cell-derived exosomes was a major cause for the superior lymphangiogenesis ability of OSCC LN1-1 cells, as laminin-332 promotes lymphatic endothelial cell migration and tube formation (Wang et al 2019a). Li et al reported that PF4V1, CXCL7, F13A1, and ApoA1 could affect OSCC lymph node metastasis, and the mechanism remains unknown (Li et al 2019a).…”
Section: Exosomes Capsuled Protein In Osccmentioning
confidence: 99%